A Comparative Study of Lunar Eclipse Calculation Astronomical Algorithm Jean Meeus and Textbook On Spherical Astronomy W.M Smart - Nur Fajriani Zar'ah; Lalu Adam Prayogi (Islamic Astronomy Department, Sharia and Law Faculty, 2025)
This research presents a comparative analysis of the lunar eclipse calculation method proposed by Jean Meeus in his textbook Astronomical Algorithms and the classical method described by W.M. Smart in his textbook Textbook on Spherical Astronomy. Lunar eclipses are celestial phenomena that can be accurately predicted using certain astronomical techniques. This research aims to evaluate the differences between modern and classical approaches in the calculation process. This research employs empirical data collection and comparison of calculation results on several lunar eclipses to evaluate the accuracy of both methods in predicting the time, duration, and phase of the eclipse. The findings are then compared with the results from NASA. This research is of the library research variety. The sources and types of data employed in this study include astronomical algorithm books and textbooks on spherical astronomy, as well as journal articles that align with the research theme. The data analysis employed by the researchers is a content analysis of the two books, then described with descriptive and comparative techniques. The principal findings of this study indicate that the two books exhibit discrepancies ranging from 3'50' to 19'18'. In comparison, the divergence with NASA results is 0'5.2', 0'10', 3'44.8', and 19'48' more rapid.